Construction and analysis of the protein interaction network between myeloid and lymphoid leukemia types - Hamad, Oras Naji (2022)
Identifying the protein-protein interactions (PPI) is a key for understanding the underlying molecular mechanisms shared between different diseases. The PPI network and the interaction mechanism between human lymphoid and myeloid leukaemia are currently absent. Since both diseases shared many similar symptoms, an investigation into the interaction would be beneficial in identifying shared proteins and understanding their PPI, thus potentially revealing novel common drug treatments. Therefore, the main purpose of this study is to identify the PPI between human lymphoid and myeloid leukaemia. Bioinformatics and computational analysis, data mining, network development and protein interaction analysis were used to create a new lymphoidamyloid PPI network. Further analysis using the Ingenuity Pathway Analysis (IPA) software was used to identify novel drug targets in the new PPI. The results revealed a new PPI that includes 76 proteins, of which 52 have yet to be studied and 24 proteins representing new physical interactions between lymphoid and myeloid leukaemia. Functional analysis of the new PPI network revealed that most of the proteins were involved in signal transduction, haemostasis, neutrophil degranulation, DNA repair, genetic transcription pathway and the immune system. Topological analysis of the new network identified the hubs and bottlenecks; P40763, IRF4, IL-6, P0t4637/ TP53, SMAD3, GSTM1, MTHFR, FASLG, BIRC3, PROM1, ITGB1, CYP2B6, CYP1A1and KMT2D as putative drug targets for future laboratory studies. The disease association analysis indicated that interaction defects in lymphoid–myeloid leukaemia is significantly associated with cancer, Type 2 diabetes and pulmonary disease. An assessment of the putative drug targets using the IPA software revealed that the drugs ocriplasmin (Jetrea©) for the treatment of symptomatic vitreomacular adhesion; bosutinib, dasatinib, ponatinib, and Src/multikinase inhibitors for the treatment of cancers; and siltuximab and tocilizumab for the treatment of multicentric Castleman disease (siltuximab), arthritis (tocilizumab), and chimeric antigen receptor (CAR) Tcell- induced cytokine-release syndrome (tocilizumab) were possible candidates for future efficacy testing for the treatment of leukaemia cases. In conclusion, the study has generated new insights regarding lymphoid–myeloid leukaemia interactions that are valuable for future proteomic studies.